Enhancing Speaking Skills through English Mini Drama Contest on Narrative Text for Junior High School - Aurelifa Haninta; Lilia Indriani; Sri Sarwanti (PANYONARA: Journal of English Education, 2026)
Abstract: Speaking skill mastery is a key component of Indonesia’s English curriculum, yet many junior high school students continue to face difficulties in speaking skills. This study aimed to improve students’ speaking skills through the implementation of English Mini Drama Contest (EMDC) using Classroom Action Research (CAR) among 31 third-year students at a junior high school in Yogyakarta, Indonesia. The data were collected through speaking tests, interviews, and observations. The speaking test rubric was validated through expert judgement involving two English education lecturers and an English teacher, while the trustworthiness of the qualitative findings was ensured through method triangulation. The results show that students’ speaking scores improve from Cycle 1 to Cycle 2. Observations also indicate increase students’ participation. Moreover, interviews with the students revealed that EMDC fostered interest, creativity, and emotional responses. The findings suggest that EMDC is a suitable classroom innovation strategy for improving students’ speaking skills, as it provides scaffolding and classroom management that create sufficient opportunities to practice the language. Future studies may investigate different types of scaffolding and classroom management practices in EMDC to further support students’ speaking development.